Effects of dibutyl phthalate on lipid metabolism in liver and hepatocytes based on PPARα/SREBP-1c/FAS/GPAT/AMPK signal pathway. (March 2021) - Zhang, Wang; Li, Jing-ya; Wei, Xiao-chen; Wang, Qian; Yang, Ji-yang; Hou, Huan; Du, Zi-wei; Wu, Xin-an
Abstract: Phateacid esters (PAEs), such as dibutyl phthalate (DBP), have been widely used and human exposure results into serious toxic effects; such as the development of fatty liver disease. In the present study, SD rat models for in vivo study (normal and fatty liver model group) and hepatocytes for in vitro study (normal and abnormal lipid metabolism model group) were established to determine the effects of DBP on liver function and discover the possible mechanisms. Meanwhile, the peroxisome proliferator activated receptor (PPARα) blocker, GW6471, with the Adenosine 5′-monophosphate (AMP)-activated protein kinase (AMPK) activator, AICAR, were applied in vitro study to clarify the role of PPARα/SREBP-1c/FAS/GPAT/AMPK signal pathway in the process. Results suggested that DBP could activate PPARα signaling pathway and affected the protein expression of SREBP, FAS and GPAT to cause hyperlipidemia and abnormal liver function. DBP also could inhibit the phosphorylation and activation of AMPK to inhibit the decomposition and metabolism of lipids. Interestingly, the effects of DBP could be alleviated by GW6471 and AICAR. Our experimental results provide reliable evidence that DBP exposure could further induce liver lipid metabolism disorder and other hepatic toxicity through PPARα/SREBP-1c/FAS/GPAT/AMPK signal pathway. Highlights: DBP could cause hepatotoxicity in normal body. Metabolic abnormal bodies are more sensitive to the toxicity of DBP. Firstly put forward the toxicity mechanism of DBP based on the PPARα/SREBP-1c/FAS/GPAT/AMPK signaling pathway. The dose of DBP herein was close to normal exposure.